ショウワキチ ニ オケル エーロゾル ノ カガク セイブン - 中谷, 周; ナカヤ, シュウ; Nakaya, Shyu (1982)
P(論文) 南極昭和基地, 環境科学棟の北東30mでミリポアフィルター(径47mm, 孔径0.45μm)上にエーロゾル試料をエアポンプで10～30m^3の大気を吸引し採取した。これらのエーロゾル試料について, フレームレス原子吸光法によりAl, Fe, Mn, Zn, Cuの微量元素を測定した。これら各元素濃度のAl濃度に対する比を, MIYAKE (Elements of Geochemistry, Maruzen, 290p, 1965)の平均地殻組成のデータを基に, 地殻の各元素濃度のAl濃度比で割って濃縮係数(E_<crust>)を求め, ZOLLER et al. (Science, 183,199,1974), DUCE et al. (Science, 187,59,1975)の南極点, 北大西洋上での測定値と比較した。Fe, Mn, Zn, Cuの濃縮係数は南半球の昭和基地, 南極点, 北半球の北大西洋上で同オーダの興味ある結果を得た。濃縮係数が10以下のFe, Mnについては, エーロゾル中のこれら元素の起源は地殻物質であると考えられる。しかし, 濃縮係数が10^2～10^3のZn, Cuについては地殻物質起源では説明困難である。1つの可能な起源として, 化石燃料の燃焼によるものではないかと考えられる。 Atmospheric aerosol samples were collected at Syowa Station, Antarctica, on a 47mm millipore filter with 0.45μm pore size, using an air-pump. Air sampling volumes ranged from 10m^3 to 30m^3,which were collected about 30m windward of the Laboratory of Environmental Science at Syowa Station. After that, all samples were stored for the analysis in laboratory. The trace elements such as Al, Fe, Mn, Zn and Cu in these samples were determined by the atomic absorption spectrophotometric method with a graphite furnace atomizer. Enrichment factor, E_<crust>, is calculated for the trace elements in atmospheric aerosol samples. Enrichment factor is defined as the element/Al ratio in atmospheric aerosol samples divided by the element/Al ratio in crustal rocks based on the table of MIYAKE (Elements of Geochemistry, Maruzen, 290p, 1965). For the trace elements such as Mn, Fe, Zn and Cu, enrichment factors at Syowa Station are the same order of magnitude as the value at the South Pole in the southern hemisphere and over the North Atlantic Ocean in the northern hemisphere reported by ZOLLER et al. (Science, 183,199,1974) and DUCE et al. (Science, 187,59,1975). From the results, enrichment factors suggest that Fe and Mn are likely to be associated with a source largely derived from crustal rocks. But, Zn and Cu have such high values for enrichment factors that a normal crustal weathering source for these elements must be ruled out. Oxides of these ...